The Astronomy and Astrophysics Review - Palla, Francesco; Huber, Martin C E.; Matteucci, Francesca; Courvoisier, Thierry; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The Astronomy and Astrophysics Review is devoted to all areas of astronomy and astrophysics, including subjects bordering on other fields. Thus developments in laboratory or particle physics directly relevant to astronomy may be included, as well as cosmic ray physics, studies in the solar system, astrobiology, instrumentation and computational and statistical methods with specific astronomical applications. It is intended that all important fields be reviewed from time to time, whereby the frequency of review will be dependent on the amount of activity in the different areas. The journal emphasizes review articles that are not only of the highest quality in their scientific content, but also have a good readability. They thereby provide an excellent starting point for scientists or students seeking access to a new or unfamiliar field as well as for researchers and lecturers in need of authoritative material in fields with which they are less familiar.
Keywords: Planetology; Astronomy; Astrophysics; Cosmology; Observations, Astronomical; Astronomy -- Observations; Space sciences; Astronomy, Astrophysics and Cosmology; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics) .; Planetology; Astrophysics and Astroparticles; Astronomy, Observations and Techniques